Employee satisfaction, human resource management practices and competitive advantage: the case of Northern Cyprus - Hamzah Elrehail; Ibrahim Harazneh; Mohammad Abuhjeeleh; Amro Alzghoul; Sakher Alnajdawi; Hussein M. Hussein Ibrahim (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to explore the impact of human resource (HR) management practices on achieving competitive advantage through studying the mediating role of employee satisfaction in the context of five-star hotels in Northern Cyprus. Design/methodology/approach To produce numeric data as well as to test the hypothesis, the researchers employed structural equation modeling and AMOS. The testing included (n=439) questionnaires. The model suggested by the authors examined the tourism sector, and in particular, five-star hotels located in Northern Cyprus. Findings The main research findings revealed that HR practices had a significant effect on competitive advantage. By comparison, the research findings revealed that the mediator variable had no effect on achieving competitive advantage for five-star hotels in Northern Cyprus. Originality/value This study demonstrates originality by responding to the recommendations of prior studies conducted on HR in Northern Cyprus Island. This makes a theoretical contribution to the field, since only Turkey recognizes Northern Cyprus, which makes conducting research on this country a challenge for researchers worldwide. Based on this study's outcomes, this paper discusses its theoretical and practical implications, as well as recommendations for future research.
Keywords: 650; Competitive advantage; Employee satisfaction; Human resource practices; Northern Cyprus